PERANAN TARI GALOMBANG BAGI KEHIDUPAN SOSIAL MASYARAKAT KOTA PADANG: STUDI KASUS PADA ACARA PESTA PERKAWINAN - Putri Amriana; Indrayuda Indrayuda (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to reveal and explain the role of Galombang dance creations in the social life of Padangnese citizen, which is used at wedding parties. This type of research was qualitative with descriptive method. The research instrument was the researcher herself as the key instrument, who was assisted by both audio and visual recording devices. The study took place in Padang; informants were dancers, choreographers, and managers of studios and user communities. Data were collected by observation, interviews, documentation studies and literature studies. Data analysis done by referring to the Miles and Huberman techniques, they are the stage of data collection, data reduction, data presentation, and verification and conclusion data. The result of the study, which is the Galombang Dance creation, currently plays a role as a wedding party ornament. Aside from being an ornament, it is also a suggestion for respect and social status. Galombang dance form is a creation of entertainment-oriented and consists of traditional. In addition, Galombang dance has an effect on the existence of its users and the two brides. Keywords: Galombang dance roles, as well as a wedding